Invasive pulmonary aspergillosis in patients with influenza infection: A retrospective study and review of the literature - Huang, Linna; Zhang, Nannan; Huang, Xu; Xiong, Shuyu; Feng, Yingying; Zhang, Yi; Li, Min; Zhan, Qingyuan (The clinical respiratory journal, 2019)
Introduction There has been a rapid increase in the number of influenza and invasive pulmonary aspergillosis (IPA) co‐infection. Objectives To explore the risk factors and predictors of a poor prognosis in influenza and IPA co‐infection. Methods We included patients with confirmed influenza during the 2017‐2018 influenza season and cases of influenza and IPA co‐infection in the literature. Results A total of 64 patients with influenza infection were admitted to ICU. Of these patients, 18 were co‐infected with IPA. Others were assigned to the control group (n = 46). A total of 45 patients from the literature were added to the IPA group (n = 63). A multivariate logistic regression suggested that influenza patients who were given steroids after ICU admission, who had a white blood count (WBC) of more than 10*109/L on ICU admission and whose CT findings manifested as multiple nodules and cavities might have a higher risk of developing IPA. Compared to survivors, non‐survivors had higher sequential organ failure assessment (SOFA) scores (16 ± 4 points vs 8 ± 4 points, P < 0.001), lower CD4+ T cell counts on ICU admission [315 (83‐466) cells/μL vs 152 (50‐220) cells/μL, P = 0.031] and more requirement extracorporeal membrane oxygenation (ECMO) support [13 (50%) vs 7 (18.9%), P = 0.015]. Conclusions Influenza patients who are given steroids after ICU admission, who have WBCs of greater than 10*109/L on ICU admission, and whose CT imaging shows multiple nodules and cavities might have a high risk of IPA. Higher SOFA scores, CD4+ T cell counts lower than 200 cells/μL on ICU admission and more ECMO requirement might be predictors of a poor prognosis.